Investigating the Causes and Consequences of Brand Attachment of Luxury Fashion Brand: the Role of Gender, Age, and Income - Endy Gunanto Marsasi; Asih Dewi Yuanita (Media Ekonomi dan Manajemen, 2023)
In recent years, luxury fashion brands have experienced drastic growth. This study examines how hedonic motivation, self-image congruence, brand experience, and brand attachment are interrelated factors driving the purchase intention of industrial luxury fashion brands. Our research aims to construct a consumer behaviour model to complete the hedonic motivation process, which influences brand attachment and is influenced by demographic factors. The research model will fully predict the proposed model to examine the effect of gender, age, and income. The survey was conducted in Indonesia with a sample of 324 respondents. Multiple group analysis SEM (Structural Equation Modelling) was used to test the model across samples. The results reveal substantial consumer behaviour disparities based on respondents' gender, age, and income level. Research findings can aid the luxury brand industry, particularly the fashion industry, in comprehending demographic differences. It is crucial to develop specific marketing strategies to promote luxury brands, influencing consumers' purchase intentions.